Importance of LINC00852/miR-145-5p in breast cancer: a bioinformatics and experimental study - Abbas Shakoori; Asghar Hosseinzadeh; Nahid Nafisi; Ramesh Omranipour; Leyla Sahebi; Nazanin Hosseinkhan; Mohsen Ahmadi; Soudeh Ghafouri-Fard; Maryam Abtin (Discover Oncology)
Abstract Purpose We aimed to examine the importance of an lncRNA, namely LINC00852, in the pathogenesis of breast cancer. Materials and methods In the current study, we used several online tools to examine the importance of LINC00852 in breast cancer. Then, we examined these findings in 50 pairs of breast cancer tissues and adjacent non-cancerous ones. We also re-evaluated the data of miR-145-5p signature from our recent study. Results While in silico tools revealed down-regulation of LINC00852 in breast cancer samples, expression assays showed significant up-regulation of this lncRNAs in breast cancer samples compared with matching control samples from Iranian patients. miR-145-5p was under-expressed in breast cancer samples compared with non-cancerous samples. LINC00852 could separate breast cancer tissues from adjacent non-malignant tissues with an AUC value of 0.7218 (P value < 0.001). Conclusion The current study potentiates LINC00852/miR-145-5p axis as a possible contributor to the pathogenesis of breast cancer.